Pharmacological and nonpharmacological treatment of tension-type headache - Łabuda, Julia; Falkowski, Dawid; Frank, Marta; Kozłowska, Magdalena; Kozłowski, Gracjan; Rewaj-Nowicka, Urszula; Szwedo, Jowita (Quality in Sport, 2025)
Introduction and purpose: Tension-type headache (TTH) is known to be the most prevalent form of primary headache with a 1-year prevalence of about 26%. About 3 billion people experienced tension type headaches or migraine in 2016. Prevalence rate appears to be highest at 35-39 years of age. Some patients suffer from chronic tension-type headaches (CTTH) when the pain appears during 15 days of a month for 3 months continuously. This review aims to summarize current knowledge in pharmacological and non-pharmacological treatment of this condition. Material and methods: Medical databases like PubMed and Google Scholar were searched for scientific papers on the pharmacological and non-pharmacological interventions in tension-type headache. These were analyzed and summarized in this review. State of knowledge: Pharmacological treatment of acute tension-type headache is based on non-steroidal anti-inflammatory drugs (NSAIDs), especially ibuprofen, and acetaminophen. For preventive treatment amitriptyline, opipramol and selective serotonin reuptake inhibitors are used. Among non-pharmacological treatments we distinguish physical methods like acupuncture, myofascial trigger points therapy, extracorporeal shockwave therapy, physical exercises (aerobic and strengthening), Transcutaneous Electrical Nerve Stimulation and yoga. Psychological therapy is an additional procedure for reducing the pain. Conclusion: However there are many possibilities of treatment both pharmacological and non-pharmacological, it is still a wide area to investigate.